Neuroprotective Properties of a Novel Non-Thiazoledinedione Partial PPAR-γ Agonist against MPTP. (2nd October 2013) - Swanson, Christine R.; Du, Eric; Johnson, Delinda A.; Johnson, Jeffrey A.; Emborg, Marina E.
Abstract : Activation of the peroxisome proliferator activated receptor-gamma (PPAR)- γ is proposed as a neuroprotective strategy to treat neurodegenerative disorders. In this study, we examined if LSN862 (LSN), a novel non-thiazoledinedione partial PPAR- γ agonist, was neuroprotective in a mouse model of Parkinson's disease (PD) and assessed possible mechanisms of action. LSN (3, 10, or 30 mg/kg) or vehicle was orally administered daily to C57BL/6 and antioxidant response element-human placental alkaline phosphatase (ARE-hPAP) reporter mice 3 days prior to 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP; 30 mg/kg, i.p. ×  5 days) or PBS administration. LSN elicited a dose-dependent preservation of dopaminergic nigrostriatal innervation that was not associated with inhibition of MPTP metabolism or activation of Nrf2-ARE, although changes in NQO1 and SOD2 mRNA were observed. A significant dose-dependent downregulation in MAC-1 and GFAP positive cells was observed in MPTP + LSN-treated mice as well as significant downregulation of mRNA expression levels of these inflammatory markers. MPTP-induced increases in PPAR- γ and PGC1 α expression were ameliorated by LSN dosing. Our results demonstrate that oral administration of LSN is neuroprotective against MPTP-induced neurodegeneration, and this effect is associated with downregulation of neuroinflammation, decreased oxidative stress, and modulation of PPAR- γ and PGC1 α expression. These results suggest that LSN can be a candidate alternative non-thiazoledinedione partial PPAR- γ agonist for neuroprotective treatment of PD.